The contribution of lean thinking to the maintenance of manufacturing systems - Davies, Christopher (Cranfield University, 2003)
Despite many significant contributions and advances of lean thinking recorded in articles, books, and industrial case studies, its impact upon the maintenance function has not been fully investigated. From a maintenance perspective, excluding TPM, little or no insight into the use of lean thinking concepts in maintenance can be found in the literature, despite prominent contributors advocating greater management and business integration. An objective of the research described in this thesis was to satisfy the need for industry to understand the contribution of lean thinking to the maintenance of manufacturing systems. A research hypothesis (lean thinking improves the effectiveness of the maintenance function) was therefore devised that aimed to bridge this gap in knowledge in which the researcher developed two new tools alongside existing methodologies for further investigation. The first novel research tool, a lean concept reference framework, was used to comprehensibly represent fe--antfiffikifig concepts possible within a company, and maintenance in particular. Ihe sec n oyýý _411 measure of maintenance performance comprised a number of indicators that sign ough ify c maintenance activity. This was used to reflect the impact of lean concept use by maintenance through change in activity performance. The research investigates the current views of lean thinking and maintenance within the UK, and particularly in the automotive industry. It exposes the diversity of maintenance as a function within this industry, and highlights the scope of lean concept use and understanding. As an outcome of the research, it was found that each company investigated had different reasons for adopting and using lean concepts within their maintenance function. Similarly, each company differed in the management and use of their performance data. Nonetheless, all those investigated accepted the role of lean concept use within maintenance, and considered certain elements useful. These elements were used as an aggregation of tools to assist maintenance in their activities rather than using them to develop an alternative maintenance strategy. However, perception of lean concept use, and the perceived benefits gained differed according to different viewpoints. Although it was generally accepted that lean use bought about or improved overall skills, and helped provide the basis of a more robust and standardised maintenance department, concern was expressed concerning the difficulty in translating essentially lean manufacturing techniques to suit maintenance.